Relations between Russia and China at the End of the 19th Century - Sobirjonovna, Shomansurova Zilola (PT. Antis International Publisher, 2024)
The article examines about the weakening of the central government in China at the end of the 19th century, the aggravation of the country’s socio-political situation, and the strengthening of the western countries’ struggle to take over it.